THE AZIMUTHAL DEPENDENCE OF SURFACE WAVE POLARIZATION IN A SLIGHTLY ANISOTROPIC MEDIUM - Tanimoto T. (My University, 2004)
Compact analytical formulae are derived for particle motions of surface waves in a weakly anisotropic, flat-layered medium. Theory only incorporates coupling between fundamental mode Rayleigh and Love waves but comparison against numerical results show that a good match is achieved for anisotropy up to approximately 10 per cent. Among various types of particle motions for Rayleigh and Love waves, it is proposed that Love wave vertical polarization, defined by the ratio of the vertical to the transverse displacement, may be a good, cleanly measurable quantity. Derived formulae show that vertical polarization contains 2θ and 4θ azimuthal dependence, similar to the well-known phase velocity variations. Formulae show depth kernels explicitly and can be used for the inversion of anisotropic parameters. The measurement of polarization as a function of azimuth then provides constraints on anisotropy under a seismic station. The derived formulae are a natural extension of Smith & Dahlen's results on phase velocity to particle motions.
Keywords: ANISOTROPY; PARTICLE MOTION; SURFACE WAVE